Effect of Fibre Mercerization on Strength Properties of Agave Cantula Roxb. Strengthen Foamed Concrete - S.S. Majeed; Md Azree O. Mydin; R. Omar; R.A. Razak; M.M. Al Bakri Abdullah; S. Ishak (Archives of Metallurgy and Materials)
Researchers are increasingly becoming fascinated by the possibilities of utilizing natural fibre, which is a byproduct of production processes, as an addition in concrete. This fibre exhibits a low density and is amenable to chemical changes. The primary aim of this research study is to examine the influence of agave cantula roxb. fibre (ACRF) in low-density foamed concrete (FC) after being subjected to different doses of alkali treatment using sodium hydroxide (NaOH). Various weight fractions of treated ACRF were employed in the FC mix, namely 0% (as the control), 1%, 2%, 3%, 4%, and 5%. FC with a density of 1060 kg/m3 was produced and subsequently tested. The three types of strength properties that have been evaluated and analysed included flexural, tensile, and compressive strengths. The findings from this study have revealed that the inclusion of 3% of treated ACRF in FC yields highly favourable results in relation to strength properties. The use of treated ACRF improves the FC’s strength characteristics, particularly its bending and tensile strength, by bridging microscopic cracks and filling up gaps. It is noteworthy to emphasize that accumulation and unequal dispersion of ACRF are possible if the weight fraction of ACRF applied above the optimal value of 3% which led to decrease in FC’s strength properties. This exploratory work will lead to a better understanding of the potential applications of treated ACRF in FC. It is critical to encourage the long-term development and implementation of FC products and technology.